The problems of work scientology applied to the workaday world - Hubbard, L. Ron (La Fayette Ron) 1911-1986.; Ramon, Monica; Hubbard, L. Ron (La Fayette Ron) 1911-1986.; Golden Era Productions; Religious Technology Center; L. Ron Hubbard Library ([Jacinto, Calif.] Religious Technology Center L. Ron Hubbard Library, 2010)
Outlines the principles and laws of Scientology that apply to every endeavor, every problem of work.
On what does success depend? -- Confusion -- The anatomy of control -- Affinity, reality and communication -- A-R-C and the tone scale -- The eight dynamics -- Exhaustion -- The one who succeeds.
Library has: VDR-976 (1 DVD) ; VDR-977 (1 DVD)
A film based on the book by L. Ron Hubbard.
Performer, Monica Ramon.
DVD
Keywords: Scientology; Job satisfaction; Work -- Psychological aspects